Performance comparison of different combined heat and compressed air energy storage systems integrated with organic Rankine cycle. (28th August 2019) - Wang, Peizi; Zhao, Pan; Lai, Yongquan; Wang, Jiangfeng; Dai, Yiping
Summary: Compressed air energy storage (CAES) is promising to enable large‐scale penetration of renewable energies (REs). However, conventional diabatic CAES (D‐CAES) depends largely on fossil fuels, while adiabatic CAES (A‐CAES) is limited in output power. To conquer these disadvantages, concept of combined heat and CAES (CH‐CAES) is proposed in this paper. The proposed system couples an electric heater with conventional A‐CAES. During charging, electricity storage transforms from pure compression to partly relying on Joule heating. The stored heat in an electric heater will be used to boost turbine inlet temperature during discharging. Consequently, system charge/discharge capacity can be improved without enlarging cavern size, raising cavern pressure, and producing greenhouse gases. This paper discusses three types of CH‐CAES systems with different electric heater installation positions. Off‐design performance analysis for each system is conducted on the basis of turbomachinery (compressors, turbines, and the pump) characteristic maps and heat exchangers off‐design models. Performance comparison is conducted between these three CH‐CAES systems (called Mode II, III, and IV for simplification) and the conventional A‐CAES system (Mode I). Control strategies are also given in this paper. Results show that the EVR (energy generated per unit volume of storage) increases with participation of an electric heater, while the RTE (system roundtrip efficiency) slightly decreases. Mode I has the highest RTE. The largest EVR appears in Mode III where the electrical heater is in series with the intercooler and after cooler. Mode II is a compromise solution to achieve both relatively high RET and EVR when the electrical heater is installed in series only with the intercooler. Mode IV with a paralleling electrical heater has great flexibility to adapt different user demands. The integration of the ORC has a positive effect on system RTE and EVR.